Cannabidiol Supplements in Romania: Bridging the Gap Between Marketed Claims and Clinical Reality - Corina Andrei; George Mihai Nitulescu; Georgiana Nitulescu; Anca Zanfirescu (Pharmacy)
In recent years, the European market, including Romania, has witnessed a significant increase in the promotion of cannabidiol (CBD)-based products, often presented as effective treatments for various health conditions. This study investigates the inconsistencies between the health claims associated with these supplements and the evidence from clinical trials. To identify products available on the Romanian market, a systematic review of online pharmacies and websites that specialize in selling CBD-based products has been performed. Additionally, a systematic review of clinical trials has been conducted to assess the efficacy of CBD for the specified indications. Our analysis revealed that some claims, such as those related to post-traumatic stress disorder, lack substantial clinical evidence. Moreover, even when clinical support exists, the dosages recommended for the supplements are often significantly lower than those used in trials, raising concerns about their efficacy. These findings highlight the need for stricter regulatory oversight and more transparent communication to ensure that consumer expectations are aligned with scientific evidence, ultimately promoting informed decision-making and consumer safety.